PP.31.07: MASKED HYPERTENSION IN PREHYPERTENSIVE SUBJECTS. (June 2015) - Camafort-Babkowski, M.; Sobrino, J.; Domenech, M.; Vinyoles, E.; Álvarez, J. S.á.nchez; Soriano, J. Rueda; Mestre, A. Riera; Torres, C. Fernandez; Vilagut, F. Trias; Camacho, F. Guerrero; Alonso, M. Baquero; Adrián, M.; et al.
Abstract : Objective: To analyze the prevalence of Masked hypertension (MHT) and their associated predictive factors in non-hypertensive subjects with high normal BP values. Design and method: 453 subjects with office BP values between 130–139mmHg of systolic BP (SBP) and / or 85–89 mmHg for diastolic BP (DBP) underwent 24-h ambulatory BP monitoring (ABPM), medical history, physical examination, EKG and laboratory investigations. Nocturnal Hypertension (NHT) was defined as BP higher or equal to 135 mmHg for SBP and / or higher or equal to 85 mmHg for DBP during day-time. Results: Mean age was 49.79 years ± 10.28 years, with a 51% of women. MHT prevalence was 41.5%. It was more frequent in younger subjects (48.5 ± 10.6 vs 50.7 ± 9.9 years; p = 0.024), with a higher proportion of males (48.2% vs 35.1%, p = 0.005) and a higher office SBP and DBP (135.1 ± 3.5 / 85.1 ± 3.4 vs 133 5 ± 5.0 / 83.7 ± 4.7 mmHg; p < 0.001). As for the laboratory and EKG investigations higher values of plasma creatinine (0.82 ± 0.17 vs 0.78 ± 0.1 mg / dl; p = 0.012) and increased left ventricular enlargement determined by the R voltage in aVL (0.49 ± 0.42 vs 0.2 ± 2.7 mV; p = 0.015) were found. Conclusions: Masked hypertension affects more than a half of prehypertensive subjects, mainly in younger males. We found in this group more target organ damage as worse renal function and increased left ventricular enlargement.